KESEHATAN MENTAL REMAJA: STUDI KUALITATIF PADA KORBAN BROKEN HOME - Nur Laila Khoirunisa; Nor Fatmah (MUHAFADZAH: Jurnal Ilmiah Bimbingan dan Konseling Islam, 2026)
The increasing phenomenon of broken homes has become a serious issue as it affects adolescents’ mental health, particularly during a vulnerable stage of psychological and social development. This study aims to analyze the mental health conditions of adolescents from broken home families, the contributing factors, and the role of Islamic Guidance and Counseling in addressing these issues. This research employs a qualitative descriptive approach with data collection techniques including interviews, observation, and documentation involving two adolescent subjects. The results indicate that both subjects experience emotional disturbances such as anxiety, sadness, and low self-esteem, as well as difficulties in social and educational aspects. These differences are influenced by parenting patterns, environmental conditions, and social support. The findings reveal that such conditions reflect social pathology caused by family disorganization, which affects adolescent development comprehensively. Therefore, Islamic Guidance and Counseling through a prayer-based approach can serve as an effective solution to help adolescents achieve inner peace, enhance self-control, and strengthen their spirituality, enabling them to cope with life challenges more adaptively.